A sequential decoding procedure for pooled quantitative measure. Issue 1 (18th May 2022) - Zhong, Yunning; Xu, Ping; Zhong, Siming; Ding, Juan
Abstract: Group testing (pooling) is a commonly used method while screening for rare diseases, especially for large-scale screening. In recent years there has been growing interest in direct analysis of quantitative measures to take advantage of full information. In this study, we develop a pooling procedure for identification of infected specimens and the measurement is quantitative. Exclusive simulations are conducted to investigate the performance of our procedure, "Qpool, " under a variety of scenarios. We also demonstrate its application in routine monitoring of Listeria monocytogenes .